Novel Applicators for Local Microwave Hyperthermia Based on Zeroth-Order Mode Resonator Metamaterial. (3rd April 2014) - Vrba, David; Vrba, Jan
Abstract : It is demonstrated that a theory of zero-order mode resonator (ZOR) metamaterial (MTM) structure can be used for the development of a novel class of applicators for microwave thermotherapy, for example, for hyperthermia in cancer treatment or for physiotherapy. The main idea of creating such an applicator is to generate and radiate a plane electromagnetic (EM) wave into the treated biological tissue, at least in a certain extent. The main aim of this paper is to investigate whether an EM wave generated by ZOR MTM structure and emitted into the biological tissue can produce a homogeneous SAR distribution in the planes parallel to the applicator aperture and achieve a penetration depth approaching the theoretical limit represented by SAR distribution and penetration depth of an ideal EM plane wave. EM field distribution inside a virtual phantom of the treated region generated by the applicator that is based on the proposed ZOR MTM principle is investigated using a well-proven full-wave commercial simulation tool. The proposed applicator type shows both a low unwanted leaked electromagnetic field and a fairly homogeneous electric field in its aperture as well as in the virtual phantom of the treated region.